Deconstructing “The Other”: Female Resistance In Great Expectations Through Simone De Beauvoir’s Lens - Yollanda Aprila Nirwana; Ruly Indra Darmawan (LPPM Universitas Advent Indonesia, 2025)
The researchers used this research to identify the forms of resistance and subordination exhibited by female characters. The research utilized a descriptive, qualitative, and feminist approach, focusing on Simone de Beauvoir's concept of Otherness in The Second Sex. Data was gathered by carefully reading and observing Great Expectations by Charles Dickens, including narration, monologue, and character behaviors. Furthermore, the researchers determined that female characters (Estella, Miss Havisham, and Biddy) lose their subjectivity as a result of the subordination of women and societal expectations that required them to conform to traditional norms in the Victorian era. Women are defined as